Adequate Materials as Pre-Requisite for Functional School Library - Egesimba, N. M.; Quadri, R.F.; Dimkpa, T.N.; Ezebuike, M.N. (Richtmann Publishing, 2011)
This paper attempts to examine the Concept of School Library its aims and functions, it also identified materials in afunctional school library to include print and non-print materials such as, fictions, text books, reference books, periodicals andnon print materials. It identified the problems of school library to include inadequate staffing, lack of information materials,infrastructures and insufficient awareness. Finally, conclusions were drawn while solutions to identified problems wererecommended.